Pengaruh Terapi Relaksasi Benson Terhadap Perubahan Stress Pada Lansia: The Effect of Benson Relaxation Therapy on Changes in Stress in the Elderly - Rere, Masni Tidore (Dohara POAJ, 2024)
Introduction: Chemotherapy can cause nausea. One effort to deal with stress itself is to use the Benson Relaxation method. Benson's Relaxation techniques contain elements of repetition of sentences or words of prayer that are repeated according to religion or belief. Methods: This study uses a Quasy Experiment design. The number of samples is 96 elderlies. Research instruments using Depression Anxiety Stress Scale 42 (DASS 42) questionnaires and statistical tests using Dependent T-tests. Results: The results showed that before giving Benson Relaxation Therapy it was found that most of the elderly had severe stress category (75,0%). After administration of Benson Relaxation Therapy most of the elderly have mild stress changes (82,3%). There is a significant influence of changes in stress in the elderly before and after administration of Benson Relaxation Therapy with a p-value of 0,000. Discussion: There is a significant influence of changes in stress in the elderly before and after administration of Benson Relaxation Therapy. Elderly who experiences complaints of severe stress and the need for increased health education in the elderly about non-pharmacological treatment in the form of Benson Relaxation Therapy techniques for the reduction of severe stress.